High‐Performance Fuel Cells Based on In2O3–La/Pr‐Doped Ceria Semiconductor–Ionic Conductor Materials Electrolyte. Issue 1 (3rd October 2019) - Xiang, Dong; Nie, Jingjing; Feng, Chu; Liu, Kai; He, Zili; Shen, Liangping; Wang, Baoyuan
Abstract : Recent investigations disclose that semiconductor–ionic conductor materials (SIMs) as novel functional materials deliver superior ionic conductivity. However, SIMs are not utilized as electrolyte membranes in traditional fuel cells due to mixed ion–electron conduction. To address this issue, a Schottky fuel cell using In2 O3 –La/Pr‐doped ceria (LCP) SIMs as the electrolyte membrane is fabricated; such devices take advantage of the superior ionic conductivity of SIMs, combined with the band energy alignment to avoid short circuiting. Through adjusting the weight ratio of In2 O3 and LCP, a supreme power density of 730 mW cm −2 is obtained for the Schottky fuel cell operated at 550 °C, which also exhibits decent performance at low temperatures, namely, a power maximum of 370 mW cm −2 even at 500 °C. The rectification curve verifies the existence of Schottky junction in the cell, the corresponding built‐in field prevents the electron from passing through the cell to eliminate short circuiting, and simultaneously promotes the ion across the interface between the electrolyte and anode. The results develop novel In2 O3 –LCP SIMs with superior conductivity and also demonstrate an efficient cell configuration based on SIMs, which proposes a potential strategy for the application of intermediate/low‐temperature solid oxide fuel cells. Abstract : Herein, the first application of In2 O3 –La/Pr‐doped ceria (LCP) semiconductor–ionic conductor materials (SIMs) as the electrolyte in a Schottky fuel cell is demonstrated. The superior ionic conductivity of SIMs and the built‐in field of Schottky junction contribute to the superior performance of fuel cells, that is, P max of 730 mW cm −2 at 550 °C and 370 mW cm −2 even at 500 °C.